The Seven Lamps of the Law - Leonard W. Brockington (Washington University Law Quarterly, 1950)
The most eloquent of those who have spoken of our profession have often talked of the law as though it were a great building, a temple, a house of many mansions. A house in whose gardens flow the streams that fertilize the mercies and purify and cleanse the conscience of mankind. Perhaps you recall as I do some of the deathless words of Daniel Webster, "Justice, Sir, is the great interest of man on earth. It is the ligament which holds civilized beings and civilized nations together. Wherever her temple stands, and so long as it is duly honoured, there is a foundation for social security, general happiness, and the improvement and progress of our race. And whoever labors on this edifice with usefulness -and distinction, whoever clears its foundations, strengthens its pillars, adorns its entablatures, or contributes to raise its august dome still higher in the skies, connects himself, in name, and fame, and character, with that which is and must be as durable as the frame of human society." And so today I am going to try what may be a foolish experiment. And I hope that you who, in this place, are taught the grave solemnity of facts, the ruthless cogency of logic, the strict science of law, will forgive me if I seem to be more concerned with heads in the clouds .than I am with feet on the earth. For after all sentiment is one of the great forces of the world and the most momentous fact can be insignificant without it.
Keywords: Jurisprudence